The Selection of the Aluminum-based Adjuvant Reconfigures the Exposure of the Target Antigen in the Multiantigenic Formulation TERAVAC - Iglesias, Enrique; Cruz, Otto (Drug Delivery Letters, 2016)
Background: Previously, we demonstrated a similar adsorption of the vaccine candidate TERAVAC against HIV-1 to the aluminum hydroxide and aluminum phosphate adjuvants but the subcutaneous administration with aluminum hydroxide promoted a better Th1 response than the aluminum phosphate. Objective: The present study examined whether a differential three-dimensional (3D) adsorption of the multiantigenic formulation TERAVAC to these adjuvants has an impact on the generation of IgG antibodies against the gp120 protein. Methods: Groups of mice were subcutaneously inoculated with TERAVAC adjuvated with aluminum hydroxide or aluminum phosphate hydrated gels. At the end of the schedule of immunization sera from animals were collected and the recognition of HIV antigens assessed by western blot. Results: We found that subcutaneous immunization of TERAVAC with aluminum hydroxide, and not with aluminum phosphate, stimulated a gp120-specific IgG response. A possible explanation for this finding is discussed. Conclusion: This result revealed a previously unappreciated difference when the multiantigenic formulation TERAVAC is inoculated with these adjuvants. Taken together, this finding and previous studies suggest that selection of the best aluminum-containing adjuvant for mixtures of antigens must be based on experimental evidences.
Keywords: Adsorption